Clinical Advances in Immunonutrition and Atherosclerosis: A Review - Ruiz-León, Ana María; Lapuente, María; Estruch, Ramon; Casas, Rosa (Frontiers in Immunology, 2019)
Atherosclerosis is a chronic low-grade inflammatory disease that affects large and medium-sized arteries and is considered to be a major underlying cause of cardiovascular disease (CVD). The high risk of mortality by atherosclerosis has led to the development of new strategies for disease prevention and management, including immunonutrition. Plant-based dietary patterns, functional foods, dietary supplements and bioactive compounds such as the Mediterranean Diet, berries, polyunsaturated fatty acids, ω-3 and ω-6, vitamins E, A, C and D, coenzyme Q10, as well as phytochemicals including isoflavones, stilbenes and sterols have been associated with improvement in atheroma plaque at an inflammatory level. However, many of these correlations have been obtained in vitro and in experimental animals models. On one hand, the present review focuses on the evidence obtained from epidemiological, dietary intervention and supplementation studies in humans supporting the role of immunonutrient supplementation and its effect on anti-inflammatory response in atherosclerotic disease. On the other hand, this review also analyzes the possible molecular mechanisms underlying the protective action of these supplements, which may lead a novel therapeutic approach to prevent or attenuate diet-related disease, such as atherosclerosis.